Progression of lamellar hole-associated epiretinal proliferation and retinal changes during long-term follow-up. Issue 1 (25th May 2017) - Compera, Denise; Schumann, Ricarda G; Cereda, Matteo G; Acquistapace, Alessandra; Lita, Viviane; Priglinger, Siegfried G; Staurenghi, Giovanni; Bottoni, Ferdinando
Abstract : Purpose: To report on progression of lamellar hole-associated epiretinal proliferation (LHEP) in eyes with lamellar macular holes (LMH) using spectral-domain optical coherence tomography (SD-OCT), and to correlate with intraretinal changes and visual function. Methods: From a retrospectively reviewed series of 167 eyes with non-full-thickness macular holes, we exclusively included a subgroup of 34 eyes with LMH and LHEP by SD-OCT evaluation. In these eyes, area of LHEP, intraretinal changes of defect diameter, central retinal thickness, defects of the ellipsoid zone and occurrence of a contractive epiretinal membrane were analysed. Additionally, clinical data were documented. Results: Area of LHEP significantly increased during a mean follow-up period of 40.5 months (median 52 months). Analysing intraretinal changes, a significant enlargement of minimum and maximum horizontal lamellar hole diameter was found that correlated with the area of LHEP. Defects of the ellipsoid zone were seen in 65% of the eyes at baseline and in 85% at the end of follow-up. Increase of maximum horizontal hole diameter and ellipsoid zone defects correlated with a decline of visual acuity. Fifty per cent of patients with LMH and LHEP also demonstrated extrafoveal typical contractive epiretinal membranes with retinal folds. Conclusions: Long-term follow-up revealed an increase of the area of LHEP in eyes with LMH that correlated with the enlargement of lamellar hole diameter and ellipsoid zone defects. Our data delineate the progression of intraretinal changes in association with a decline of visual function in this subgroup of LMH eyes.